Sinuscalide A: An Antiviral Norcembranoid with an 8/8-Fused Carbon Scaffold from the South China Sea Soft Coral Sinularia scabra - Liu, Jing; Tang, Qi; Huang, Jian; Li, Te; Ouyang, Han; Lin, Wen-han; Yan, Xiao-jun; Yan, Xia; He, Shan (Journal of organic chemistry, 2022)
Sinuscalide A (1), featuring an uncommon 8/8-fused carbon scaffold, three new norditerpenes, sinuscalides B–D (2–4), and sinuscatone A (5), with a 5/4/9 tricyclic carbon ring system, along with four known compounds were isolated from the South China Sea soft coral Sinularia scabra. The structures of the new compounds were established by extensive spectroscopic analysis, X-ray diffraction, and electronic circular dichroism (ECD). A plausible biosynthetic pathway for 1 was proposed. In a bioassay, compound 1 showed antiviral activity against human enterovirus EV71 (IC50 = 5.0 μM) and an inhibitory effect against RANKL-induced osteoclastogenesis (92.3% inhibition at 10 μM). Compound 5 exhibited mild inhibition against Streptococcus pneumoniae and Salmonella paratyph (MIC 16 μg/mL).